2005
DOI: 10.1016/j.cardiores.2005.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin promotes endothelial progenitor cell proliferative and adhesive properties in a PI 3-kinase-dependent manner

Abstract: Chronic Epo treatment is associated with an increase in the adhesive and proliferative properties of circulating EPC in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 36 publications
7
73
0
7
Order By: Relevance
“…There is long-standing evidence that expression of erythropoietin receptors is not restricted to erythroid precursors in the marrow but is also detectable in nonerythroid tissues, including neurons, adipocytes, and vascular endothelium (37). There is also evidence that erythropoietin affects vascular endothelial function and influences angiogenesis (38)(39)(40)(41)(42). Hence, nonerythropoietic effects of epoetin, particularly at high pharmacologic blood levels, could have a role in promoting adverse clinical events associated with epoetin treatment in patients with kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is long-standing evidence that expression of erythropoietin receptors is not restricted to erythroid precursors in the marrow but is also detectable in nonerythroid tissues, including neurons, adipocytes, and vascular endothelium (37). There is also evidence that erythropoietin affects vascular endothelial function and influences angiogenesis (38)(39)(40)(41)(42). Hence, nonerythropoietic effects of epoetin, particularly at high pharmacologic blood levels, could have a role in promoting adverse clinical events associated with epoetin treatment in patients with kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Even treatment with erythropoietin seems to have beneficial effects on the functional properties of EPCs in both animals and humans [30] , while a study of Iwakura and colleagues showed an increase in the mobilization of EPCs after treatment with estradiol [31] .…”
Section: Endothelium Dysfunction and Cardiovascular Diseases: Role Ofmentioning
confidence: 99%
“…8 Although possible EPO production in renal tubular cells was reported previously 9, 10 a more recent study has shown that fibroblast-like cells in the corticomedullary interstitium of the kidney synthesize EPO, while tubular cells do not. 8 Proliferative effect of EPO on several progenitor cells including erythroid progenitor cells, [11][12][13] endothelial progenitor cells (EPC), 14,15 cardiomyogenic stem cells 37 has been reported. EPO is known to act specifically on haematopoietical cells, however recent evidence demonstrated several non-haematopoietical effects.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of cultured endothelial cells with rHuEPO resulted in cell proliferation and differentiation into vascular structures. 15 George et al 14 reported that EPC proliferative effect of EPO is dose dependent, it was evident at low doses such as 1 U/ml and lost at higher doses such as 25 U/ml. Moreover, addition of EPO, dose dependently increased EPC adhesion to fibronectin, cultured endothelial cells and cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation